PENGARUH PROFITABILITAS, LEVERAGE, DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR FARMASI YANG TERDAFTAR DI BEI - Sinta Kurnia; Nani Rohaeni; Ade Samsinar (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
Tax Avoidane is an effort to reduce tax legally to reduce or even eliminate the tax burden. The purpose of this study was to determine the effect of profitability ratios, leverage, and sales growth on tax avoidance in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses a quantitative method with a descriptive statistical approach. The population in this study were 12 companies with a sample of 8 pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique in this study used purposive sampling, with a research time of 5 years and 40 data were obtained. The results of this study show that partially the profitability variables proxied by ROA and leverage as proxied by DER have a significant effect on tax avoidance, and sales growth has a negative effect on tax avoidance, while profitability as proxied by ROE and leverage as proxied by DAR has no effect on tax. avoidance. However, simultaneously variable X1, X2,  X3,  X4 and X5 had  significant effect on variable Y